ANALISIS PENYAJIAN LAPORAN KEUANGAN BERDASARKAN PENERAPAN STANDAR AKUNTANSI KEUANGAN ENTITAS TANPA AKUNTABILITAS PUBLIK PADA PT. FORTUNA INTI ALAM - Tangkau, Pricilia R. E.; Sondakh, Jullie J.; Suwetja, I Gede (GOING CONCERN : JURNAL RISET AKUNTANSI, 2017)
VAT is one part of the tax applicable in Indonesia. CV. Salber Marine & Mining as a company engaged in the trade of goods subject to VAT, as in general make a purchase with Input Tax which may be credited and not credited. The purpose of this study is to know whether  the application of VAT and VAT underpayment or over payment in accordance with Law of VAT  No. 42 Tahun 2009 article 9. This study used a qualitative descriptive method. The type of data used is the qualitative and quantitative data, while the source of the data used is secondary data. Methods of data collection is done with documentation and literature study. The Company will record, calculation payment and report the delivery of value added tax in the Notice Period of Value Added Tax (VAT Period SPT). Conclusion is that the application of VAT in the recording does not record all the activities of the company completely and appropriately but in the  calculation payment and reporting of CV. Salber Marine & Mining was almost in accordance with the VAT Act applied and through the application of VAT, namely the purchase and sale of taxable goods so that the sum of the difference by the number of Input Tax to Output Tax generate VAT Less / More Pay at the end of each month, it is in accordance with the Law of VAT No. 42 of 2009 article 9.Key Words: Value Added Tax (VAT), Input Tax, Output Tax.